THE INFLUENCE OF THE COOPERATIVE SCRIPT METHOD ON SELF-CONFIDENCE AND ITS IMPACT ON STUDENTS’ PUBLIC SPEAKING SKILLS - Rofiqul Majid; Maghfiroh, Lailatul; Alfin, Jauharoti (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
Abstract This research aims to examine the relationship of the cooperative script method in increasing self-confidence and its impact on public speaking skills. This study used path analysis with 37 students as the sample. Data collection was through a questionnaire to assess learning methods, self-confidence, and public speaking skills. The data were analyzed through linear regression and Sobel tests. The results showed that 1) The cooperative script method had an influence on students’ self-confidence; 2) Students’ self-confidence had an influence on their public speaking skills; 3) The cooperative script method did not have a significant direct effect on students’ public speaking skills so that the cooperative script method has an indirect effect on students’ public speaking skills through self-confidence as a mediating variable. Therefore, to improve public speaking skills indirectly, learning methods or models that affect self-confidence are needed because self-confidence is one of the components that can affect students’ public speaking skills.